Słów kilka o baśni tureckiej na podstawie tekstów Ağlayan Nar ile Gülen Ayva oraz Yeşil Kuş - Florek, Joanna (Studia Azjatystyczne, 2019)
The article presents a state of Turkish research and the most common classification systemising tales as a literary genre in Turkish literary studies. The article discusses the most popular theories about the origin of tales. By showing two examples of tales, it provides answers to the following questions: Are Turkish tales different from the European ones? Does religion have impact on folk literature? What are the most popular types of Turkish tales? And how can we describe the main characters in Turkish tales?